Isolated Soft Switching Current Fed Series LC Resonant DC-DC Convertor for Electrical Vehicle Application - et.al, Anand Sharma (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current fed series resonant converter for electrical vehicle application is offered in this paper. The converter is able to achieve ZVS for primary side semiconductor switches. In the overlap time of voltage and current at zero crossing series resonant tank circuit is gives short interval of resonant pulse. This resonant pulse provide natural voltage decrease for semiconductor switches and voltage pulse is zero earlier compare to current across switches and ZVS achieve for semiconductor switches. All devices turn off softly so dependency on snubber is decreased to clamp the voltage across the switches. Presented converter reduce the circulating current so switching losses is decreased and converter efficiency will improvise. The proposed converter is simulated in MATLAB Simulink environment to investigate and analyses the proposed converter.